ANALISIS BANJIR WAY BESAI DENGAN MODEL MATEMATIS UNSTEADY FLOW MENGGUNAKAN SOFTWARE HEC - RAS - Harijadi Harijadi (UNIVERSITAS LAMPUNG, 2015)
River flood control work involving them are two important analysis i.e. analysis of hydrologic and hydraulic analysis. In the analysis of hydrologic calculation of discharge, the draft is one of the main objectives in the work of flood control of the river. The calculation of design discharge dis- charge based on data available on the river concerned or through the calculation of the design of rain then converted to discharge draft with empirical equations. On the other hand, the analysis of the hydraulics are also important do to the needs of the design capacity of discharge capacity of the river against a draft that would pass. This research was conducted on the analysis of the hydraulics for the River Way Besai using HEC- RAS which is a continuation of the analysis of hydrology. In the analysis of hydrology, on condi- tion there is no measurement data field, bankfull capacity of the river used as a calibration mate- rial for Q2. The disadvantages of calculation of flood discharge using rain data is that we should always assume that rain occurred in the entire WATERSHED. As a result of discharge produced sometimes too big or over estimated. Analysis of hydrologic and hydraulic analysis in Indonesia is still basically approaches is supported with logical reasons. Therefore the project work experience is a very important asset that will affect the accuracy of the analysis.